Experimental study on the heat balance of turbocharged marine diesel engines with variable coolant flow. (2nd December 2022) - Zhang, Bo; Zhang, Ping; Zeng, Fanming
ABSTRACT: An engine heat balance experiment was conducted to analyse the influence of the freshwater pump speed on the overall performance of the diesel engine. At low and medium loads, appropriately reducing the coolant flow could reduce the fuel consumption rate and improve the effective power. At the rated load, when the pump speed was 2000 r/min, the diesel power and fuel economy were optimal. Under overload conditions, appropriately increasing the coolant flow could improve the fuel economy. The zone between the two exhaust valves of the cylinder head (Point C) had the highest thermal load. At medium loads—when the pump speed was 1600 r/min—the Point C temperature was close to the creep temperature. At rated and overload loads—when the pump speed was less than 2200 r/min—the Point C temperature entered the creep temperature range. The experimental results provided a theoretical basis for intelligent cooling control strategies..